Optimalisasi Pembukuan Digital : Sosialisasi dan Pendampingan Akuntansi bagi UMKM Warung Kopi di Kota Kediri - Handani, Ranisa Ristya; Wafa, Zaenal (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This Community Service (PKM) activity aims to enhance the capacity of MSME actors in managing finances more effectively by optimizing the digital bookkeeping system. The method of implementing this activity is carried out systematically with a participatory and collaborative approach for one month at three partner locations in Kediri City. This activity involves educational activities and practical assistance using the Daily Expenditure Cash Book and Youtap POS Digital Cashier applications. The results of the socialization and assistance activities for digital bookkeeping show that the digitalization of financial recording has a positive impact on improving the quality of their financial management in small businesses. Before the program was implemented, the majority of MSME actors still used an unstructured manual system, making cash flow quality control more difficult. Through the implementation of the financial management application, business actors were able to record transactions in real-time, prepare simple financial reports, and periodically understand their financial conditions. This program requires collaborative support from various parties through advanced training and expanding access to technology.